2007
DOI: 10.1021/cc0600831
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Enhanced Raman Spectroscopic-Encoded Beads for Multiplex Immunoassay

Abstract: A new type of encoded bead, which uses surface-enhanced Raman scattering (SERS), is described for multiplex immunoassays. Silver nanoparticles were embedded in sulfonated polystyrene (PS) beads via a polyol method, and they were used as SERS-active substrates. Raman-label organic compounds such as 4-methylbenzenethiol (4-MT), 2-naphthalenethiol (2-NT), and benzenethiol (BT) were then adsorbed onto the silver nanoparticles in the sulfonated PS bead. Although only three kinds of encoding have been demonstrated h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
59
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(59 citation statements)
references
References 64 publications
0
59
0
Order By: Relevance
“…For example, Jun et al (2007) have proposed SERS-encoded polystyrene (PS) beads containing Raman active small compound labeled silver nanoparticles with a silica shell, enabling them to obtain reproducible spectra for multiple samples. As another example, Grubisha et al (2003) have also demonstrated the detection of prostate specific antigen using a sandwich immunoassay based on SERS.…”
Section: Technologies For Multiplexed Sers Detectionmentioning
confidence: 99%
“…For example, Jun et al (2007) have proposed SERS-encoded polystyrene (PS) beads containing Raman active small compound labeled silver nanoparticles with a silica shell, enabling them to obtain reproducible spectra for multiple samples. As another example, Grubisha et al (2003) have also demonstrated the detection of prostate specific antigen using a sandwich immunoassay based on SERS.…”
Section: Technologies For Multiplexed Sers Detectionmentioning
confidence: 99%
“…As encapsulating agent, polymers (Stokes et al, 2006) and silica (Jun et al, 2007) are generally employed. Indeed, silica encapsulated SERS tags are being commercialized.…”
Section: Chemical Sensing Based On Inelastic Light Scattering: Sersmentioning
confidence: 99%
“…43 (a) Schematic diagram of dot-coded particle synthesis showing polymerization across two adjacent laminar streams to make single-probe, halffluorescent particles (shown in b); (c) diagrammatic representation of particle features for encoding and analyte detection. encoding scheme shown allows the generation of 2 20 (1,048,576) unique codes; (d) differential interference contrast (DIC) image of particles generated by using the scheme shown in (a); (e-g) overlap of fluorescence and DIC images of single-probe (e), multiprobe (f, bottom), and probe-gradient (g, left) encoded particles. A schematic representation of multiprobe particles is also shown (f, top) and a plot of fluorescent intensity along the center line of a gradient particle (g, right).…”
mentioning
confidence: 99%
“…However, surface-enhanced Raman signal-based assays are limited by their relatively weak Raman signal, thus requiring amplification of the signal while maintaining an optimal signal-to-noise ratio. 20 …”
mentioning
confidence: 99%